Analysis of Video CODEC Performance Using Different Softphone Applications - Dandun Kusuma Yudha; Ahmad Ashari (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2021)
In a video call there are several components, such as IP phone or softphone, CODEC, and server. Selection of softphone and CODEC is a consideration in building a video communication network because it will affect the quality of video call. This research compare the quality of video calls based on softphone application and CODEC combination. The quality measured by QoS, PSNR, and MOS parameters.Softphone applications examined in this research are Blink, Zoiper, MicroSIP, PortGo, Linphone, and X-Lite. CODEC examined in this research are H.264, VP8, H.263+, and H.263. Each softphone application will be combined with a CODEC that is native to the softphone. There are nine combinations of softphone application and CODEC.Based on the research results, CODEC H.264 has the best performance when paired with the Blink softphone application. CODEC VP8 has the best performance when paired with the Zoiper softphone application. The H.263+ CODEC has the best performance when paired with the PortGo softphone application. The H.263 CODEC and X-Lite softphone applications have the worst test results but still get “good” grades when tested using QoS, PSNR, and MOS parameters.